2012
DOI: 10.1177/1938640011433828
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Osteotomy for Symptomatic Bunionette Deformity Is Not Advisable for Severe Deformities

Abstract: Bunionette, or tailor's bunion, is a painful protrusion on the plantar and/or lateral aspect of the fifth metatarsal head. Until recently, there have been very good results reported in literature when minimally invasive therapy is used to treat this deformity. In this study, the authors critically review the outcome of patients operated by the minimal invasive technique. A total of 31 feet were retrospectively reviewed with a mean follow-up of 52 months (range 14-106 months). The results were related to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…good for high-grade bunionette deformities. 24 We believe this is because the minimally invasive techniques, including distal osteotomies, do not address the pathology responsible for more severe deformities, which include lateral bowing in cases of type II deformities and an increased 4-5 IMA in cases of type III deformities. 1,2,5 One common concern about proximal fifth metatarsal osteotomies is the tenuous metatarsal blood supply.…”
Section: Metatarsophalangeal (Mtp) Anglementioning
confidence: 99%
See 1 more Smart Citation
“…good for high-grade bunionette deformities. 24 We believe this is because the minimally invasive techniques, including distal osteotomies, do not address the pathology responsible for more severe deformities, which include lateral bowing in cases of type II deformities and an increased 4-5 IMA in cases of type III deformities. 1,2,5 One common concern about proximal fifth metatarsal osteotomies is the tenuous metatarsal blood supply.…”
Section: Metatarsophalangeal (Mtp) Anglementioning
confidence: 99%
“…3,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Recently, minimal invasive treatment has been increasingly used with generally good published results, but a recent study has questioned these findings especially for types II and III deformities. 13,20,[22][23][24] The purpose of this study was to report the results of the reverse Ludloff osteotomy for the treatment of types II and III bunionette deformities in a cohort of patients.…”
mentioning
confidence: 99%
“…After evaluating abstracts and full-text reviews, 9 articles were included in this review, for a total of 327 feet in 249 patients, with a mean age of 45.35 years and a male-female ratio of 37:212. [27][28][29][30][31][32][33][34][35] The mean follow-up time was 51.95 months. All studies had a level of evidence of IV.…”
Section: Resultsmentioning
confidence: 99%
“…Only 1 study reported differences between bunionette classification and clinical and radiographic results, reporting inferior results in feet with stage II and III deformity than in type I classification with distal osteotomy (subcapital from lateral-proximal to medial-distal). 34 The authors suggested that a diaphyseal osteotomy should be done in type II cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation